2011
DOI: 10.1371/journal.pntd.0001166
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Protective Efficacy and Marked Polymorphism Limits the Value of Schistosoma japonicum Tetraspanin-2 as a Vaccine Target

Abstract: Background Schistosoma mansoni tetraspanin 2 (Sm-TSP-2) has been shown to be strongly recognized by IgG1 and IgG3 antibodies from individuals putatively resistant to schistosome infection, but not chronically infected people, and to induce high levels of protection against challenge infection in the murine model of schistosomiasis. Amplification by PCR of homologous sequences from male and female S. japonicum worms showed the presence of 7 different clusters or subclasses of S. japonicum TSP-2. We determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…Novel TSPs may thus have evolved to fulfill the highly diverse requirements of distinct parasite stages. In this context, it is worth noting that TSPs have been assayed as vaccine antigens for schistosomiasis [126], [127] and primary alveolar echinococcosis [119] in mouse models. In both systems, some level of protection was observed upon immunization with particular TSPs.…”
Section: Resultsmentioning
confidence: 99%
“…Novel TSPs may thus have evolved to fulfill the highly diverse requirements of distinct parasite stages. In this context, it is worth noting that TSPs have been assayed as vaccine antigens for schistosomiasis [126], [127] and primary alveolar echinococcosis [119] in mouse models. In both systems, some level of protection was observed upon immunization with particular TSPs.…”
Section: Resultsmentioning
confidence: 99%
“…When BmALT-2 was combined with BmHSP12.6 (14) and BmTSP-LEL as a multivalent fusion vaccine, close to 95% protection were achieved in mouse and gerbil models (15). Gene polymorphism has been reported for TSP-2 from S. japonicum (27,28). However, to date there are no reports on the gene polymorphism of B. malayi or W. bancrofti TSP-2.…”
Section: Discussionmentioning
confidence: 99%
“…On invading a mammalian host, schistosomes have evolved several mechanisms to adapt to, and survive in, the hostile host environment; in particular, they develop a unique syncytial tegument, as well as mechanisms of antigenic mimicry [33], immune modulation [68] and evasion [69, 70]. In this study, we found extracellular matrix constituents, that are located in the tegumental protein assemblage, were enriched in hepatic schistosomula.…”
Section: Resultsmentioning
confidence: 96%